Empowering Creativity: Assessing the Impact of Inquiry-Based Learning in Creative Writing Performances - Nguyen Thi Thao, Uyen; Pham Quang, Binh (International Journal of English Language and Pedagogy, 2024)
Inquiry-Based Learning (IBL) is an effective approach for enhancing students' creative writing skills. This study aims to examine whether the IBL method has an impact on student's creative writing performances specifically within the framework of Vietnam. The study utilized the mixed methods research design, which enables the researchers to obtain quantitative data from pre-test and post-test for investigating the effects of IBL instruction on students' writing performances. The experimental group and the control group were administered two 2-hour sessions per week for a total of eight weeks. The pre- and post-tests were administered to gather data on the students' written performance, prior to and following the intervention. Although the results indicated that IBL and the traditional teaching method had a significant impact on students, the analysis of students' writing portfolios revealed that the inquiry-based learning class demonstrated more enhanced aspects of creative writing, showcasing increased creativity in their language use and writing. Furthermore, the results of the analysis revealed IBL can serve as a powerful tool for cultivating creativity in writing classrooms in Vietnam.